Austria's economic relations with the EU Eastern Partnership countries and Russia - Vasily Astrov (The Vienna Institute for International Economic Studies (wiiw), 2024)
The dynamics of Austria's economic relations with the EU Eastern Partnership (EaP) countries - Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine - and with Russia have deviated from those of the EU in several important ways. During the decade preceding the war in Ukraine, Austrian trade with the region generally developed less dynamically than EU trade, as trade with countries that did not sign Deep and Comprehensive Free Trade Agreements (DCFTAs) with the EU - unsurprisingly - underperformed. However, Austrian investments in Russia have shown greater resilience than EU investments, especially since the start of the war in Ukraine. Austria ranks third from bottom among EU member states for the share of companies that have completely withdrawn from Russia or are in the process of doing so, probably explaining in part why its exports to Russia have suffered much less than EU exports. In addition, chemicals, including pharmaceuticals, which have been little affected by sanctions, account for a large share of Austrian exports. Also, unlike the EU, Austria's dependence on Russian natural gas remains high, partly for geographical reasons and also because of contractual obligations between Austria's ÖMV and Russia's Gazprom. Austria would be well advised to build on its record of economic involvement in the EaP region and capitalise on the new opportunities offered by the improved EU accession prospects of Ukraine, Moldova and Georgia.
Keywords: F14; F21; Q40; 330; EU Eastern Partnership countries; Austria; EU; trade; investment; gas dependence